Immunotherapeutic modification of Escherichia coli peritonitis and bacteremia by Iris kashmiriana baker - Wagay, Javeed Iqbal; Jain, Kirti (Journal of Drug Delivery and Therapeutics, 2018)
A larger number of medicinal plants and their purified constituents have been shown beneficial therapeutic potentials. We present here the protective effects of an Indian medicinal plant Iris Kashmiriana as compared to Ofloxacin in E. coli induced peritonitis. Iris Kashmiriana is one of an important member of family Iridaceae, locally known as Mazarmund in Kashmir. The plant has been widely used in traditional medicine and modern clinical preparations to treat cold, flu, malaria, toothache, cancer, bacterial, viral infections and bruise. Rats were pre-treated with 200 mg/kg and 400 mg/kg/bwt dose for 3 days and fourth day with E. coli (1×108 CFU/ml) strain and consecutively 3 days treatment. Mortality was monitored for 14 days. After the death of rats or completion of the experiment rats were sacrifice and kidney were used for our protocol. Colonies were count and statically analysis was done. Results showed dose dependent anti-microbial activity. Pretreatment of mice with Iris Kashmiriana improved bacterial clearance as well as improved phagocytic and intracellular bactericidal capacities of neutrophils. In the Ofloxacin treated mice although bacterial clearance was rapid, polymorph phagocytosis was depressed. Thus the results, obtained justify the traditional use of Iris Kashmiriana. Keywords: Iris kashmiriana, E. coli induced peritonitis, Neutrophils, Ofloxacin.